(untitled) - Keyes, Joan Ross (New York, 1998)
A picture dictionary (in American English) designed for ages five to seven. It can be used by itself or with accompanying components as the core of an entire picture dictionary programme. Over 700 words are presented in the context of pictures that tell stories. Five characters and their families appear throughout the book in interesting and amusing everyday situations. The book presents 60 topics.
Keywords: English language,English language,English language; Study and teaching,Textbooks for foreign speakers,Vocabulary